EFEKTIFITAS PENJATUHAN PIDANA TERHADAP TINDAK PIDANA NARKOTIKA DIKAITKAN DENGAN TUJUAN PEMIDANAAN - AFRIANDA, WAWAN; Edorita, Widia; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
This narcotic crime in Kampar regency from year to year the number of cases, suspects and victims are always victims of drug-related crime has increased sharply, both in terms of quality and quantity. At the time of this particular criminal offense to narcotics law enforcement and legal certainty has not been enjoyed by people of Indonesia The number of criminal cases of narcotics is seemingly much to give a negative impression that the law can not provide a deterrent effect against perpetrators, whereas the purpose of punishment is to give deterrent effect to the perpetrators.This type of research can be classified by the type of juridical sociological research, because this research author directly conduct of a study on the location or point examined in order to provide a complete and clear picture of the issues examined. This research was conducted in Kampar, while the sample population is a whole party with regard to the issues examined in this study. Source of data used, primary data and secondary and tertiary of data, data collection techniques in this study by observation, interview and literature study.From this research, there are two main things that can be inferred. First, In the criminal punishment of the effectiveness of the criminal punishment against the convict narcotics can be drawn two conclusions that criminal punishment of the first portion of former inmates of narcotic can make and feel deterrent not to repeat his actions and could be said to be effective and the achievement of a goal pemidanaannya, Second, as is known, and based on that crime is viewed from any angle can not be tolerated and left in social life because the drug can leave addictive effects and can damage organs if used in excess and drugs can also damage the nation and the state. Institutions in charge of organizing the judicial court can not do and produce a work without hooking themselves on the roles of the various components of social and community environments that shape it. In responding to the narcotic crime, there are three roles that are less cooperation in combating trafficking and abuse of narcotic drugs and make the ineffectiveness of punishment is the role of the family, the role of the social environment, the role of each individual member of the community.Keywords: effectiveness, narcotics, purpose of punishment